Designing “Simpresent Game” Application for Advanced Level of English Learners - Ahmad Alex Zakaria; Yuyun Bahtiar; Akhmad Kanzul Fikri (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
English is the main communication capital in international relations One way to master English to prepare generations to compete in the global market is to learn English in a variety of ways in addition to mastering and qualified English skills, teachers also need to master children's English teaching skills so that learning is not boring. There are many obstacles in conveying English with correct grammar, especially the communication of tense materials, it is necessary to continuously develop techniques and methods or techniques in order to easily learn reading skills, especially grammar and tense. Based on the results of the needs analysis, the researcher intends to develop several tenses for learning media. This study examines the use of the “Simpresent Game” for maximizing learning in Madrasah Aliyah Mambaul Ulum Megaluh Jombang, and used qualitative descriptive as a data analysis technique. A study was conducted in 2021 with a total of 10 subjects. Data were obtained through interviews and questionnaires. The results show that the media can influence the enthusiasm in learning tense and make them more excited in understanding the material. Through “Simpresent Game”, the students or teacher can evaluate the English learning.